2022
DOI: 10.1016/j.anl.2021.04.005
|View full text |Cite
|
Sign up to set email alerts
|

Development of infectious mononucleosis as an unusual manifestation of COVID-19

Abstract: It has generally been reported that patients with COVID-19 show a fever, cough, and/or respiratory failure as the most common clinical symptoms but some have unusual symptoms, such as anosmia, diarrhea, and throat pain. We herein report a 26-year-old woman with chief complaints of lymphadenopathy and a fever. First, she underwent a laboratory examination, which showed a high proportion of atypical lymphocytes (19%) and an increase in hepatic enzyme activities, and was then hospitalized with a diagnosis of infe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 19 publications
1
1
0
Order By: Relevance
“…García-Martínez et al reported a case of SARS-CoV-2 and EBV coinfection in a 19-year-old French woman who received symptomatic treatment, similar to our case [5]. Fukuda et al also reported an IM case as an atypical symptom of COVID-19 [6]. In their case report, similar to the typical IM caused by EBV, an increase in liver deviation enzyme levels and a marked increase in atypical lymphocyte count were observed.…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…García-Martínez et al reported a case of SARS-CoV-2 and EBV coinfection in a 19-year-old French woman who received symptomatic treatment, similar to our case [5]. Fukuda et al also reported an IM case as an atypical symptom of COVID-19 [6]. In their case report, similar to the typical IM caused by EBV, an increase in liver deviation enzyme levels and a marked increase in atypical lymphocyte count were observed.…”
Section: Discussionsupporting
confidence: 84%
“…Despite the patient presenting only a few of the typical COVID-19 symptoms, polymerase chain reaction (PCR) performed before admission showed SARS-CoV-2 positivity. Although there are some reports of Epstein-Barr virus (EBV) reactivation due to SARS-CoV-2 infection [1][2][3][4], there are few reports on the co-occurrence of COVID-19 and IM [5,6].…”
Section: Introductionmentioning
confidence: 99%